P34 Defining a target profile for promoting smoking cessation in Italy. (16th November 2010) - Bietta, C; Ferrante, G; Minardi, V; Spizzichino, L; Vasselli, S
Abstract : Background: In Italy, smoking cessation programmes rarely consider the characteristics of people who make quit attempts during life (independently from quitting or still smoking) as an useful starting point for effective intervention. Behavioural risk factor surveillance systems can provide information about sociodemographic and health profile of smokers who express intention to quit smoking and therefore represent a potential target of cessation treatment and health promotion intervention. Objective: To evaluate the percentage of people who reported smoking cessation or at least an attempt once in the last 12 months; to investigate the association between the attempt and sociodemographic, behavioural and clinical variables. Methods: Data collected in 2008 from PASSI, the Italian behavioural risk factor surveillance system based on telephone interviews of residents aged 18–69 years, were analysed to identify factors associated to quit smoking attempts. Results: Sample analysed included 18 281 current and ex-smokers. Around two out of three people (11 881) tried to quit smoking and among them 3911 (34%) failed the attempt. A multivariate analysis showed that smoking cessation attempt was more likely among males, elder (50–69 years) and married people; among those living with children (<14 yrs), with a temporary job, without economic difficulties and with a high level of education; among those with cardiovascular risk factors (hypertension, hypercholesterolaemia, obesity) and those affected by chronic diseases (almost one among cancer, diabetes and myocardial infarction). On the other side, sedentary people and those with good perceived health status are less intentioned to quit. Stratification by sex showed a different strength of association between the outcome variable and other variables in males and females, but most important that education and perceived health status are not associated with the attempt to quit smoking among women. Conclusions: Population-based surveillance system tracking the characteristics of ex and current smokers, who tried to quit, may offer a lot of information, otherwise not available, for planning, implementing and evaluating promotion and prevention interventions to support people who try to quit smoking.